Aridity-induced energy reallocation from green to brown food webs predicts grassland carbon storage - Bingbing Wan; Andrew D. Barnes; Malte Jochum; Xiaoyun Chen; Kara Allen; Junneng Yao; Nianpeng He; Feng Hu; Manqiang Liu (Proceedings of the National Academy of Sciences, 2026)
Increasing aridity is predicted to alter the structure and functioning of soil food webs, yet its impacts on grassland food-web energetics and the resulting consequences for soil carbon sequestration remain poorly understood. Here, we quantified energy fluxes in soil food webs along a natural aridity gradient using data from 240 observations across 30 grassland ecosystems in the eastern Eurasian Steppe, spanning temperate (Loess and Inner Mongolian Plateaus) and alpine (Tibetan Plateau) regions. We found that increasing aridity decreases total energy flux through whole food webs across all study regions, largely driven by species losses and weakened trophic interactions. Energy flux to herbivory-based “green” channels declined more sharply than microbivory-based “brown” channels with increasing aridity, resulting in greater dominance of brown energy channels under more arid conditions across temperate grasslands. This broad-scale “browning” of soil food webs aligns with declining soil organic carbon (SOC) storage in temperate grasslands, suggesting that carbon loss through decomposition outpaces plant-derived carbon inputs under increasing aridity. In contrast, alpine grasslands showed increased SOC when the energy flux ratio of herbivory to microbivory was below the threshold of ~1, likely because lower temperatures constrain microbe-based decomposition and energy transfer to microbivory channels under more arid conditions. Understanding the context-dependent metabolic processes that underlie energy reallocation across soil food webs can augment modeling efforts to predict change to Earth’s carbon cycle.